2014
DOI: 10.1371/journal.pone.0098081
|View full text |Cite
|
Sign up to set email alerts
|

A Panel of Serum Biomarkers Differentiates IgA Nephropathy from Other Renal Diseases

Abstract: Background and ObjectivesThere is increasing evidence that galactose-deficient IgA1 (Gd-IgA1) and Gd-IgA1-containing immune complexes are important for the pathogenesis of IgA nephropathy (IgAN). In the present study, we assessed a novel noninvasive multi-biomarker approach in the diagnostic test for IgAN.Materials and MethodsWe compared serum levels of IgA, IgG, Gd-IgA1, Gd-IgA1-specific IgG and Gd-IgA1-specific IgA in 135 IgAN patients, 79 patients with non-IgAN chronic kidney disease (CKD) controls and 106 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 33 publications
4
100
0
Order By: Relevance
“…Anti-Gd-IgA1 IgG, or IgA antibodies, were found to be associated with a risk for progression, dialysis or death [30] and this was confirmed in an international study [16]. Notably, IgG anti-Gd-IgA1 can be detected in patients with or without high levels of Gd-IgA1.…”
Section: Biomarkers Specific To Iganmentioning
confidence: 74%
See 1 more Smart Citation
“…Anti-Gd-IgA1 IgG, or IgA antibodies, were found to be associated with a risk for progression, dialysis or death [30] and this was confirmed in an international study [16]. Notably, IgG anti-Gd-IgA1 can be detected in patients with or without high levels of Gd-IgA1.…”
Section: Biomarkers Specific To Iganmentioning
confidence: 74%
“…In patients with IgAN there is a high frequency of O-glycans consisting of GalNAc alone due to defective galactosylation (Gd-IgA1) [1,2]. Although Gd-IgA1 is a rather sensitive and specific marker for IgAN, as reported by most studies (with a sensitivity of 56-76 % and a specificity of 89-94 %) [14][15][16], discrepancies exist likely because of the technical pitfalls for detecting Gd-IgA1 based on lectin binding assays [17]. The development of a monoclonal antibody specific to Gd-IgA1 could offer a new appropriate biomarker [18]; however, using this specific test, only one third of IgAN patients had values higher than those of other diseases.…”
Section: Biomarkers Specific To Iganmentioning
confidence: 99%
“…The glycosylation deficiency of IgA1 is O-glycosylation, which is characterized by a decrease in the degree of galactose modification at the end of GalNAc but direct sialylation by ST6GalNAc-II [18]. Therefore, the smooth docking and correct localization of glycosyltransferase in Golgi is one of the crucial factors for the IgA1 glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…My colleagues Yanagawa and Suzuki et al [33] compared serum levels of IgA, IgG, Gd-IgA1, Gd-IgA1-specific IgG and Gd-IgA1-specific IgA in 135 IgA nephropathy patients, 79 patients with non-IgA nephropathy CKD and 106 healthy controls. Serum was collected at the time of renal biopsy from all IgA nephropathy and CKD patients.…”
Section: Iga Nephropathymentioning
confidence: 99%
“…Therefore, it can be concluded that serum levels of Gd-IgA1-specific antibodies are elevated in most IgA nephropathy patients, and their assessment, together with serum levels of Gd-IgA1, improves the specificity of the assays. Our observations suggest that a panel of serum biomarkers may be helpful in differentiating IgA nephropathy from other glomerular diseases [33]. …”
Section: Iga Nephropathymentioning
confidence: 99%